2022
DOI: 10.3389/fphys.2022.850180
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Ovarian and Tubal Ectopic Pregnancy After IVF-ET: Case Report and Literature Review

Abstract: Ovarian pregnancy (OP) coupled with tubal ectopic pregnancy is rare. We present a case of coexistent ovarian and tubal ectopic pregnancies in the same adnexa resulting from in vitro fertilization and embryo transfer (IVF-ET) for tubal occlusion. The patient presented with mild vaginal bleeding without abdominal pain. OP was diagnosed via sonographic findings of an ectopic gestational sac (GS) and yolk sac that seemed to be inside her left ovary. Laparoscopic exploration confirmed this diagnosis, and ipsilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although the rate of dual ovarian and tubal ectopic pregnancies is unknown, we can infer these cases likely occur even more infrequently than ovarian pregnancies with rates of 0.5%–3.2%, 1 and spontaneous bilateral tubal pregnancies with rates of 0.06%–0.14% of all ectopic pregnancies 2 . Previous reports of dual ovarian and tubal ectopic pregnancies in the literature are rare, and most case reports described their occurrence following ovarian induction 3–7 . Risk factors for extrauterine pregnancies include previous ectopic pregnancy, history of surgical manipulation of the tubes, genital infections, infertility and assisted reproductive technology (ART) 8,9 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the rate of dual ovarian and tubal ectopic pregnancies is unknown, we can infer these cases likely occur even more infrequently than ovarian pregnancies with rates of 0.5%–3.2%, 1 and spontaneous bilateral tubal pregnancies with rates of 0.06%–0.14% of all ectopic pregnancies 2 . Previous reports of dual ovarian and tubal ectopic pregnancies in the literature are rare, and most case reports described their occurrence following ovarian induction 3–7 . Risk factors for extrauterine pregnancies include previous ectopic pregnancy, history of surgical manipulation of the tubes, genital infections, infertility and assisted reproductive technology (ART) 8,9 .…”
Section: Discussionmentioning
confidence: 96%
“…2 Previous reports of dual ovarian and tubal ectopic pregnancies in the literature are rare, and most case reports described their occurrence following ovarian induction. [3][4][5][6][7] Risk factors for extrauterine pregnancies include previous ectopic pregnancy, history of surgical manipulation of the tubes, genital infections, infertility and assisted reproductive technology (ART). 8,9 Our patient had no history of ovulatory stimulation and only reported a remote history of chlamydia infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although ovarian pregnancies in the second ( Hwang et al, 2020 ) or even third trimester of pregnancy ( Prabhala et al, 2015 ) have been reported, most ovarian pregnancies are found in the first trimester ( Thanasa et al, 2022 ; Huang et al, 2022 ). Most of the patients were treated because of abdominal pain or intraperitoneal hemorrhage secondary to ovarian pregnancy rupture.…”
Section: Discussionmentioning
confidence: 99%
“…[9] In addition, the use of ovulation-inducing drugs and ovarian stimulation increases uterine contractility and embryo sac migration to the fallopian tube and ovary. [10] 4. Diagnosis…”
Section: In Vitro Fertilization-embryo Transfermentioning
confidence: 99%